The Influence of Price Discount and Store Atmosphere on Consumer Purchase Decisions at Equator Stores in Bengkulu City - Monica Gustia; Ade Tiara Yulinda (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of price discount and store atmosphere on purchasing decisions at the Khatulistiwa Store, Bengkulu city. The sample in this study were 120 consumers who shop at the Khatulistiwa store, Bengkulu city. The data collection technique used a questionnaire. The analysis technique used is multiple linear regression, coefficient of determination and hypothesis testing. The results showed the regression equation with a positive direction, namely Y = 11.928 + 0.400X1 + 0.186 X2. This means that if the price discount and store atmosphere increase, the purchase decision will also increase. The coefficient of determination of the Adjusted R square is 0.143. This means that X1 (Price discount) and X2 (Store atmosphare) affect the purchase decision (Y) by 14.3%, while the rest 85.7% is influenced by other contributing factors. not examined in this study. Hypothesis test results show that the price discount has a significant effect on purchasing decisions at the Equator Stores, Bengkulu City with a significant value of 0.000. This illustrates that the higher the price discount given by the Khatulistiwa Store in Bengkulu city, the purchase decision will increase. Store atmosphare has a significant influence on purchasing decisions at the Khatulistiwa Store in Bengkulu city with a significant value of 0.025. This illustrates that the store's atmosphere in the Khatulistiwa Store in Bengkulu city can increase purchasing decisions. Together, the price discount and store atmosphare have a significant influence on purchasing decisions at the Khatulistiwa Store, Bengkulu city.